Necesidad de incorporar el secuestro extorsivo como delito autónomo en el Código Penal Peruano, Arequipa 2018 - Fernandez Peixoto, Sarita Hortencia (2017)
The Patrimonial Rate represent those economic contributions to the home of both spouses; which; for the Law of choice; can carry out in company; that is to say; both spouses assume the same rights and obligations; or; in separated form; every spouse contributes what it sees for suitably and; is subject of rights and obligations of an independent way; Aspect that turns out to be extremely important since; the Law of choice protected; it would counter come to the juridical nature of the Marriage. The economic contribution that is realized in community is named A Patrimonial Regime of Company of Joint property; juridical Figure typified in our country; in the Civil Code; which establishes that; the spouses administer and have; I concern of the social goods(Since also; are recognized goods of every spouse); together; any of the two being able represent to the company indistinctly. To the dissolution of this community and economic contribution of separated form; in which every spouse answers independently; there is named Patrimonial Regime of Separation of Heritages; which is characterized essentially because; inside this one; every spouse preserves to fullness the property; administration and disposition of his present and future goods; beside him belong the fruits and products of the above mentioned goods; as is the Civil Code typifies it. The present Thesis; respect of this Law of choice of the Patrimonial Rate in the Marriage; is precisely on what it was centring; provided that; controversy has generated respect of the incidents of this Law; which; in his exercise it would be denaturalizing juridically to the Marriage for concepts of; to counter come the definition that has applied; per centuries; on the Marriage: That of COMMUNITY. Besides the fact that; the Law of Choice that is had on the Patrimonial Rate; before or during the Marriage; we support; it represents relevant manifest to create mistrust of for what pair it decides to contract nuptials; placing hereby a barrier for the suitable development of the conjugal and familiar life. It is for it that; there was appearing the possible applicable norm referred to the Patrimonial Rate; which there arranges the obligatory nature of the Patrimonial Regime Company of Joint property; in such a way that; this Institution does not become stateless juridically.